Borrowing Agreement with Slovak Republic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
In light of the multilateral effort to ensure the adequacy of the financial resources available to the International Monetary Fund, and with a view to supporting the Fund's ability to provide timely and effective balance of payments assistance to its members, the Slovak Republic agrees to lend to the Fund an SDR-denominated amount up to the equivalent of EUR 440 million, on the terms and conditions set in this policy paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Slovak Republic